Rural-urban transformation in Nigeria - Sackey, James; Liverpool-Tasie, Lenis Saweda O.; Salau, Sheu; Awoyemi, Taiwo (Pennsylvania State University Press, 2012)
Since the late 1960s, Nigeria's structural and rural-urban transformations have been driven largely by developments in its oil sector. Due to increased oil revenues, incentives for the production of internationally tradable agricultural commodities declined and the agricultural sector stagnated. Incentives to produce domestically consumed agricultural products also declined as oil exports financed increasing food imports. The decline of the agricultural sector fueled rural-urban migration. Migration continued into the 1980s and 1990s, even when large parts of the economy - including manufacturing - collapsed due to lower oil prices, unsustainable policies, and foreign debt. Growth in the urban informal sector, fueled by migrants has posed challenges in terms of urban poverty and the growth of urban and peri-urban slums. The government of Nigeria has attempted to stem the tide of rural-urban migration through rural development programs. However these programs have had limited impact and were unable to stem the flow of migrants into urban areas. Key remaining questions center on how to increase productivity in the agricultural sector and at the same time provide more lucrative opportunities in urban areas.